(untitled) (Belügyi Szemle, 2025)
Aim: This study aims to explore and summarise nearly a decade of the operations of the second-generation Schengen evaluations, along with the direct experiences related to its implementation. Methodology: Professional, semi-structured interviews, document analysis, and content analysis. Findings: The comprehensive Commission report published in 2020 was of strategic importance in analysing the first five-year programme of the Schengen evaluation system, examining the operational efficiency and coherence of the Schengen area. Significant hindering factors emerged during the implementation of the previous evaluation system, such as the slow administrative processes, the burden on member states, and the lack of expert preparedness. The original objectives of the evaluation mechanism, such as dynamism and speed, were not fully achieved, which was further hampered by the slow administrative processes of the Commission. The renewal of the Schengen mechanism became unavoidable from 2021. Value: The study can contribute to the scientific understanding of the reasons and processes that justified the reform of the second-generation Schengen evaluations.